Questionnaire based assessment of teaching effectiveness during a lecture series on pharmacotherapeutics - Balani, Naresh D.; Bachewar, Narendra Prabhakar; Khan, Zeshan (International Journal of Research in Medical Sciences, 2017)
Background: Lecture is a widely accepted method of teaching & learning. It provides more of surface learning and covers larger text in specified time. However it has a disadvantage that there is no assessment about the extent of knowledge learner receives. Hence, we designed a daily questionnaire based evaluation technique. Methods: Without disclosing the topic, second year MBBS students (mean n=23) after learning from lecture series in Pharmacology, participated voluntarily to a questionnaire based task on eight therapeutic lecture topics. They wrote answers separately in 5-10 minutes before, and after delivery of text without referring to notes i. e. pre-test & post-test. Papers were valued on score basis, data recorded, interpreted and analyzed. Results: Mean acceptability (81.4%), mean improvement (94%), mean collective maximum score (96%), mean individual maximum score (92%) were observed. 85-100% participants out of total 184 in eight therapeutic lecture topics passed in post-test (None passing in Pre-test) reflected good improvement in cognitive structure. Conclusion: Performance in such tests provides feedback on teaching effectiveness, specificity & adequacy of knowledge gained by learners.